Program Gerakan Masyarakat Hidup Sehat (Germas) dan Deteksi Dini Penyakit Tidak Menular (PTM) - Aminuddin; Supetran, I Wayan; Masudin; Linda, Linda; Ramadhan, Kadar (Poltekita: Jurnal Pengabdian Masyarakat, 2020)
Effective prevention and control of PTM requires effective interaction between health care facilities from the primary level to the referral level, which includes promotive, curative, palliative and rehabilitative prevention of PTM cases. All first-level health service facilities must be staged in stages to be able to manage PTM in an integrated manner with a focus on families. The aim of the activity is to increase awareness, willingness and the ability of people to behave in healthy living and early detection of non-communicable diseases. Methods lectures, questions and answers, blood pressure measurement, blood sugar testing, gout, measurement of body weight, height, fruit eating movements and stretching exercises. Target audience Age â‰¥ 15 years and over, obesity has a history of suffering from hypertension and DM. The number of participants is 56. The results of this community service showed that out of 56 people, 25% had a waist circumference >90cm, identified 66% had hypertension, 39.3% identified symptoms of diabetes mellitus until they were identified as having diabetes mellitus. Conclusion not all people willing to do a health check. It is recommended to the health department so that the results of community service activities can be followed up by the Health Service through the nearest Puskesmas so that people who are detected as having non-communicable diseases (PTM) can be immediately dealt with.